GS Custodianship Boston Bank of the Philippines (An Information Systems Study) - Antigua, Marcial III; Garcia, Emmanuel Blaise; Itchon, Concepcion; Laya, Ana Maria (College of Engineering, 1989)
The system in study is the Government Securities (GS) Custodianship System of Boston Bank of the Philippines located at the Head Office. This system is of vital interest especially to management because it is here where a major product of Boston Bank is maintained and handled both in physical and accounting terms. This product is the Central Bank-issued treasury bills. The processing of transaction regarding treasury bills is very critical since these are very high valued products. The accuracy of processing the information and data involved with these products may actually determine the loss or profit of the bank. Consequently, the information and data used affect the efficiency of the operation and the quality of the decisions made in the day-today-operations of the system.